A Website-based Information System Design of SME Development Facilitation Registration - Sudirman, Iman; Sunaryo, Indryati; Aisha, Atya; Monang, Joe; Prasetyo, Ilham Reza (Universitas Nusantara PGRI Kediri, 2021)
Small and medium enterprises (SMEs) are particularly important for the economy of West Java Province. Accordingly, The Industry and Trade Agency of West Java Province has conducted a number of facilitation programs to support the development of these SMEs. Neverheless, the implementation of facilitation programs is faced with some major problems, for example, the registration system for applying and proposing facilitation programs is still manually managed. As a result, some SMEs do not have the opportunity to propose and receive facilitation programs from the agency in addition to the several serious issues encountered by the agency to evaluate the facilitation programs. This study aims to design a website-based information system of SME development facilitation registration in the Industry and Trade Agency of West Java Province Government, Indonesia. It used the Waterfall method to develop the system. The results suggested that the system can well run as expected. In addition, the result of usability test indicates that the proposed system can be classified as acceptable because its score is 80.4.